Shariah Criminal Offences In Syndicate Marriage From The Perspective Of Islamic Family Law (Federal Territories) Act 1984 - Haliza A Shukor; Intan Nadia Ghulam Khan; Hasnizam Hashim; Nabilah Yusof (CLJ Legal Network Sdn Bhd, 2024)
Non-Indexed Publication